Optimisation of hepatocellular carcinoma surveillance in patients with viral hepatitis: a quality improvement study. Issue 7 (11th July 2013) - Kennedy, N. A.; Rodgers, A.; Altus, R.; McCormick, R.; Wundke, R.; Wigg, A. J.
Abstract Background Surveillance for hepatocellular carcinoma (HCC) with 6‐monthly ultrasound is a standard of care for higher‐risk patients with viral hepatitis. Adherence to screening guidelines is an important quality indicator in hepatology, but multiple studies have demonstrated poor HCC surveillance practices in real‐world settings. Aims The aim of this project was to audit and then optimise HCC surveillance of viral hepatitis patients, who fulfilled criteria for screening, associated with a large tertiary hospital. Methods: Clinical practice improvement principles were utilised. A baseline audit of 22 consecutive viral hepatitis patients was performed. Major barriers preventing adequate surveillance were identified and three interventions to improve adherence to guidelines were introduced. These included: improved doctor education, system redesign and improved patient education. The effects of interventions were measured by serial random audits of patients. A final audit occurred over 3 years after the initial baseline audit. Results At baseline, 46% and 0% of patients had appropriate surveillance performed during the prior 6 months (one surveillance cycle) and 2 years (four surveillance cycles) respectively. Three years after initiation of these strategies, a final audit revealed 92% (vs 46% at baseline) and 64% (vs 0% at baseline) of patients had appropriate HCC surveillance performed during the preceding 6 months and 2 years intervals respectively (P < 0.001 in each case). Conclusions Simple and low‐cost interventions can considerably improve the clinical effectiveness of HCC screening programmes in real world settings. Clinical practice improvement principles appear to be a valid methodology for achieving this positive change.